Journal of Geophysics -Zeitschrift für Geophysik 42 - Dieminger, Walter; Untied, J. (Springer, Berlin, 1976)
Dieser Band enthält 64 Artikel zu Themengebieten der Geophysik, veröffentlicht durch die Deutsche Geophysikalische Gesellschaft in den Jahren 1976 und 1977. Inhaltsverzeichnis: Journal of Geophysics 42 Short-Time Variations of Solar Particle Fluxes during the August 1972 Events (Kremser, G., Riedler, W., Kirsch, E.) Auroral Lyman-Alpha Emission (Dose, V., Schmocker, U., Sele, G.) The Gravity Field of Northeastern Iceland (Schleusener, A., Torge, W., Drewes, H.) Parabolic Field Dependence of Kinks Occurring in the Logarithmic Time Plots of Viscous Magnetization (Markert, H., Heller, F., Steigenberger, N.) Postulated Rotation of Corsica not Confirmed by New Palaeomagnetic Data (Storetvedt, K. M., Petersen, N.) Magnetic Anomalies of the African Red Sea Shelf and Their Implications for the Anomalies of Atlantic Continental Margin (Roeser, H. A.) Self-Reversal above Room Temperature due to N-Type Magnetization in Basalt (Schult, A.) Further Utilization of the Fluxgate Magnetometer in the Palaeomagnetic Laboratory (Hummervoll, R.) Note on the Reliability of Subjective Processing of Geomagnetic Pulsation-Records in the Range Pc 2–Pc 5 (Korschunow, A.) Die Gesteinsradioaktivität und ihr Einfluß auf das Temperaturfeld in der kontinentalen Kruste (Rybach, L.) A Lithospheric Seismic Profile in Britain (Kaminski, W., Bamford, D., Faber, S., Jacob, B., Nunn, K., Prodehl, C.) Rayleigh Channel Waves for the In-Seam Seismic Detection of Discontinuities (Dresen, L., Freystätter, S.) Ultrasonic Modelling of a Moving Source (Behle, A., Rohde, J.) Propagation of Love-Type Waves in Heterogeneous Elastic Layers (Biswas, A.) Representation and Interpretation of Resistivity Mapping Data in Groundwater Prospecting in Zambia (Töpfer, K. D.) The Iranian Long Period Array (ILPA) (Akasheh, B., Eshghi, I., Soltanian, R.) Appearance of the Atmospheric Scatter Field during a Solar Eclipse (Gerharz, R.) Technique for Simultaneous Observation of Gravity and Vertical Gradient Data (Thyssen-Bornemisza, S.) Modern Standards for Gravity Surveys ...